Perception and Expectation of EFL Students on Ideal Online Learning: A Survey Study in an Indonesian Islamic Higher Education - Soni Ariawan (ITScience (Information Technology and Science), 2021)
The present study is aimed to investigate EFL students’ perception on the use of Google Classroom as an online learning platform and their expectation on an ideal online learning. 112 EFL students at State Islamic University of Mataram responded the survey study which was designed with open-ended questions. Students’ responses were qualitatively analyzed to find the main themes and sub-themes. The finding reveals that most students, 67%, perceived the use of Google classroom negatively due to the potential problems such as technical and financial problems that lead to misunderstanding on materials delivered by the teachers. On the other hand, 27% of the students have a positive perception in terms of the ease of use and its flexibility and accessibility. The least perception from the students is neutral especially from those who play safe by perceiving the perception from both positive and negative side. Furthermore, the students proposed an ideal online learning that employ an effective teaching method and curriculum, provide such complete facilities as well combine both online and offline mode (blended learning).